ChemInform Abstract: Axial‐to‐Central Chirality Transfer in Cyclization Processes. Issue 1 (7th January 2014) - Campolo, Damien; Gastaldi, Stephane; Roussel, Christian; Bertrand, Michele P.; Nechab, Malek
Abstract Review: 213 refs.